In situ RT-PCR Optimized for Electron Microscopy Allows Description of Subcellular Morphology of Target mRNA-Expressing Cells in the Brain - Cubas-Nuñez, Laura; Duran-Moreno, María; Castillo-Villalba, Jessica; Fuentes-Maestre, Jorge; Casanova, Bonaventura; García-Verdugo, José M.; Gil-Perotín, Sara (Frontiers in Cellular Neuroscience, 2017)
In situ RT-PCR detects and amplifies mRNA (cDNA) while obtaining spatial information of gene expression. When the intended use is an ultrastructural analysis of morphology, the procedure may be technically challenging and quality of tissue dramatically altered by proteolytic digestion and extreme astringency and temperature conditions. We describe a low-damaging protocol of in situ RT-PCR combined to conventional electron microscopy that preserves fine morphology, increases sensitivity, and decreases costs and complexity associated to RNA probes.